Exploring mental well-being, the emotional impact of visual impairment and experiences of prejudice and discrimination among adults from minority ethnic communities in the UK - Nikki Heinze; Claire L. Castle; Claire L. Castle (Frontiers Media S.A., 2023)
BackgroundVisual impairment (V.I.) has been associated with a negative impact on mental health outcomes, including a process of grief among those who lose their sight. Older adults with V.I. who had experienced discrimination have been found to be at increased risk of depression, loneliness, poorer life satisfaction and poorer quality of life. Adults from minority ethnic communities (MEC) may be at increased risk of V.I. and yet, research on the experiences of MEC adults with V.I. remains limited. This article forms part of a series which explores issues and status among MEC adults living with V.I. in the UK.MethodsA secondary analysis of V.I. Lives survey data was performed to explore mental well-being assessed by the short Warwick-Edinburgh Mental Well-being scale (SWEMWBS), the emotional impact of V.I., and prejudice and discrimination among a matched control sample of 77 MEC and 77 adults from white communities (WC). Participants were matched by age, gender, UK region and urban/rural setting. Subgroup analyses were also conducted for the two largest MEC subgroups, Asian (n = 46) and black participants (n = 22).ResultsThere were few statistically significant differences between the groups. MEC participants were significantly more likely than WC participants to rate emotional support to come to terms with their V.I. as important and to feel optimistic about their V.I. but they were significantly less likely to agree that they were receiving the level of emotional support they needed to get on with their life. Within the MEC group, participants from Asian communities had significantly poorer mental well-being, and they were also significantly more likely to agree that the general public were often prejudiced against people with V.I. and less likely to feel optimistic about their V.I. than black participants.ConclusionAlthough there were few statistically significant differences, participants from Asian communities were more likely to report poor mental and emotional well-being, and experiences of discrimination, than black and white participants. In contrast, participants from black communities fared the same as, or in some cases better than, white participants. Future research will need to confirm these findings and explore reasons for these.